HUBUNGAN POWER OTOT TUNGKAI DAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL SMASH BOLA VOLI TIM EKSTRAKURIKULER PUTRA SMA NEGERI 3 TUALANG - Saputra, Hendra; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to find out the correlation of limb muscle power and shoulder muscle power toward the volleyball smash result of male student extracuricular team SMA Negeri 3 Tualang. Population of this 14 male student extracuricular team in SMA Negeri 3 Tualang. This research was done on April 28, 2016 in SMA Negeri 3 Tualang volley ball field. Data analysis techniques used corelation analysis. Based on the results of data analysis can be seen that there was correlation between leg muscle power toward the volley ball smash result of male student extracuricular team which were rcalculate=0,313>rtable=0,553, there was relation between arm and shoulder muscle power toward the volley ball smash result of male student extracuricular team which were rcalculate=0,559>rtable=0,553 and there was relation among leg muscle power and arm and shoulder muscle power toward the volley ball smash result which were Rhitung=0,592>Rtabel=0,553. It can be concluded that the of limb muscle power and arm and shoulder muscle power have relation toward the volleyball smash result of male student extracuricular team SMA Negeri 3 Tulang.Key Words : leg muscle power, arm and shoulder muscle power, volley ball smash result